Short Communication: Some additions to powdery mildews (Erysiphales: Fungi) of Northwestern Himalayas - AJAY KUMAR GAUTAM; SHUBHI AVASTHI (Nusantara Bioscience, 2017)
Gautam AK, Avasthi S. 2017. Short Communication: Some additions to powdery mildews (Erysiphales: Fungi) of Northwestern Himalayas. Nusantara Bioscience 9: 52-56. During the regular mycological collections, between October to December 2015 in North-West Himalayas of Himachal Pradesh, four powdery mildews parasitic on higher plants were gathered. After study they were found to be Pseudoidium cryptolepidis on Cryptolepis buchanani, Erysiphe trifoliorum on Trifolium repentis, Podosphaera xanthii on Coreopsis lanceolata and Podosphaera euphorbiae-hirtae on Euphorbia hirta. All the powdery mildew fungi are additions to Himachal Pradesh as well as north-west Himalayas.